2018
DOI: 10.1016/j.jcma.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of code stroke on thrombolytic therapy in patients with acute ischemic stroke at a secondary referral hospital in Taiwan

Abstract: Code stroke is effective in reducing in-hospital delays. The accuracy of code stroke activation has acceptable sensitivity but low specificity. Rapid patient assessment by neurologists increases the number of patients eligible for thrombolytic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In the study of Huang et al in China, the mean CT scan time was 28 minutes, the mean time to rst visit patients according to Code 724 was 10 minutes, and the mean rTPA injection time was 116 minutes (34). In the study of Hsiao et al, the mean time to rst visit was 6 ± minutes, the mean patient arrival time to thrombolytic injection was 63 ± 23 minutes, and the mean time of arrival to brain imaging was 11 ± 7 minutes (35). Ayromlou et al in Tabriz, Iran, found the mean time of CT scan and patients' arrival to the hospital as 91 minutes, which was 66 minutes longer than the international guidelines.…”
Section: Discussionmentioning
confidence: 97%
“…In the study of Huang et al in China, the mean CT scan time was 28 minutes, the mean time to rst visit patients according to Code 724 was 10 minutes, and the mean rTPA injection time was 116 minutes (34). In the study of Hsiao et al, the mean time to rst visit was 6 ± minutes, the mean patient arrival time to thrombolytic injection was 63 ± 23 minutes, and the mean time of arrival to brain imaging was 11 ± 7 minutes (35). Ayromlou et al in Tabriz, Iran, found the mean time of CT scan and patients' arrival to the hospital as 91 minutes, which was 66 minutes longer than the international guidelines.…”
Section: Discussionmentioning
confidence: 97%
“…Huang's et al study in China, the mean time to rst visit in code 724 patients was 10 minutes, the mean CT scan time was 28 minutes, and the mean rTPA injection time was 116 minutes (34). In the study of Hsiao et al, the mean time to rst visit was 6 ± 2 minutes, the mean time of arrival to brain imaging was 11 ± 7 minutes, and mean patient arrival time to thrombolytic injection was 63 ± 23 minutes (35). In the study of Ayromlou et al in Tabriz, Iran, the mean time of patients' arrival to the hospital and CT scan was 91 minutes, which was 66 minutes longer than the international guidelines, and the mean time of patients' arrival to the hospital and receiving rTPA was 147 minutes, 87 minutes longer compared to the international guidelines (20).…”
Section: Discussionmentioning
confidence: 97%
“…We did not compare the seasonal variations in CE stroke prevalence among different areas in Taiwan; for instance, in southern Taiwan (nearly 350 km away from the study location), the monthly change in mean temperature is narrow, ranging from 19.7 to 29.4 • C. Fourth, the rates of patients receiving IVT (6.5%) and EVT (2.5%) treatments in this study were relatively low. Through serial interventions for reducing in-hospital treatment delays and the continuous updating of applicable guidelines [40], the IVT rates at the index hospital have increased from 3.2% in 2011 to 14% in 2023. A formal EVT treatment program was launched at the index hospital in May 2017.…”
Section: Discussionmentioning
confidence: 99%